Safety Targets for Urban Air Mobility Vehicles : From a perspective of Third Party Risk due to UAM operations in the Netherlands - Cheung, Y.S.; Geest, P.J. van der; Birgelen, T.M. van; Choi, J. (Nanyang Technological University, Singapore, 2024)
Urban Air Mobility (UAM) initiatives are developed with the intention to enhance personal transport in congested area of a large city. The UAM vehicles are characterised by distributed, electrically driven propulsion and corresponding advanced flight control systems. The Special Condition Vertical Take-Off and Landing (SC-VTOL) recently published by European Union Aviation Safety Agency (EASA) provides the certification requirements for these new UAM vehicles. The SC-VTOL indicates that the current Certification Standard CS-23 (small aircraft) acceptable means of compliance are no longer considered appropriate for determining the aircraft and system safety objectives. Instead, the system safety objectives for CS-25/CS-29 (large aircraft/helicopters) aircraft should be maintained as a minimum for UAM using VTOL aircraft to address the risks to persons on board and on the ground. An analysis of third party risk (risk to people on ground), based on a use case with a vertiport located in the centre of a city, is made to demonstrate whether or not this SC-VTOL can enable a sizeable volume of UAM traffic over a congested area of a city by taking into account the third party safety objectives. Results of Individual Risk and Societal Risk calculations show that limited traffic volume is only achievable by taking additional measures.